Genetic lesions of the noradrenergic system trigger induction of oxidative stress and inflammation in the ventral midbrain - Barut, Justyna; Rafa-Zabłocka, Katarzyna; Jurga, Agnieszka M.; Bagińska, Monika; Nalepa, Irena; Parlato, Rosanna; Kreiner, Grzegorz (Neurochemistry international, 2022)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by motor deficits caused by the loss of dopaminergic neurons in the substantia nigra (SN) and ventral tegmental area (VTA). However, clinical data revealed that not only the dopaminergic system is affected in PD. Postmortem studies showed degeneration of noradrenergic cells in the locus coeruleus (LC) to an even greater extent than that observed in the SN/VTA. Pharmacological models support the concept that modification of noradrenergic transmission can influence the PD-like phenotype induced by neurotoxins. Nevertheless, there are no existing data on animal models regarding the distant impact of noradrenergic degeneration on intact SN/VTA neurons. The aim of this study was to create a transgenic mouse model with endogenously evoked progressive degeneration restricted to noradrenergic neurons and investigate its long-term impact on the dopaminergic system. To this end, we selectively ablated the transcription initiation factor-IA (TIF-IA) in neurons expressing dopamine β-hydroxylase (DBH) by the Cre-loxP system. This mutation mimics a condition of nucleolar stress affecting neuronal survival. TIF-IADbhCre mice were characterized by selective, progressive degeneration of noradrenergic neurons, followed by phenotypic alterations associated with sympathetic system impairment. Our studies did not show any loss of tyrosine hydroxylase (TH)-positive cells in the SN/VTA of mutant mice; however, we observed increased indices of oxidative stress, enhanced markers of glial cell activation, inflammatory processes and isolated degenerating cells positive for FluoroJade C. These results were supported by gene expression profiling of VTA and SN from TIF-IADbhCre mice, revealing that 34 out of 246 significantly regulated genes in the SN/VTA were related to PD. Overall, our results shed new light on the possible negative influence of noradrenergic degeneration on dopaminergic neurons, reinforcing the neuroprotective role of noradrenaline.
Gesehen am 29.08.2022